Improved Retention With 6-Month Clinic Return Intervals for Stable Human Immunodeficiency Virus-Infected Patients in Zambia. (24th August 2017) - Mody, Aaloke; Roy, Monika; Sikombe, Kombatende; Savory, Thea; Holmes, Charles; Bolton-Moore, Carolyn; Padian, Nancy; Sikazwe, Izukanji; Geng, Elvin
Abstract : Six-month clinic return intervals were associated with decreased lateness, gaps in medication, and loss to follow-up in stable human immunodeficiency virus–infected patients in Lusaka, Zambia, when adjusting for patient characteristics and prior retention history compared to 3- and 1-month intervals. Abstract: Background: Extending appointment intervals for stable HIV–infected patients in sub-Saharan Africa can reduce patient opportunity costs and decongest overcrowded facilities. Methods: We analyzed a cohort of stable HIV-infected adults (on treatment with CD4 >200 cells/μL for more than 6 months) who presented for clinic visits in Lusaka, Zambia. We used multilevel, mixed-effects logistic regression adjusting for patient characteristics, including prior retention, to assess the association between scheduled appointment intervals and subsequent missed visits (>14 days late to next visit), gaps in medication (>14 days late to next pharmacy refill), and loss to follow-up (LTFU; >90 days late to next visit). Results: A total of 62084 patients (66.6% female, median age 38, median CD4 438 cells/μL) made 501281 visits while stable on antiretroviral therapy. Most visits were scheduled around 1-month (25.0% clinical, 44.4% pharmacy) or 3-month intervals (49.8% clinical, 35.2% pharmacy), with fewer patients scheduled at 6-month intervals (10.3% clinical, 0.4% pharmacy). After adjustment and compared to patients scheduled to return in 1 month, patients with six-month clinic return intervals were the least likely to miss visits (adjusted odds ratio [aOR], 0.20; 95% confidence interval [CI], 0.17–0.24); miss medication pickups (aOR, 0.47; 95% CI 0.39–0.57), and become LTFU prior to the next visit (aOR, 0.41; 95% CI, 0.31–0.54). Conclusions: Six-month clinic return intervals were associated with decreased lateness, gaps in medication, and LTFU in stable HIV-infected patients and may represent a promising strategy to reduce patient burdens and decongest clinics.